Ireland during the Second World War : Farewell to Plato's Cave - Evans, Bryce (Book collections on Project MUSE., 2014)
In the first book detailing the social and economic history of Ireland during the Second World War, Bryce Evans reveals the hidden story of the Irish Emergency. If the diplomatic history of Irish neutrality is familiar, the realities of everyday life are much less so. This work provides a clear summary of Ireland's economic survival at the time as well as an indispensable overview of every published work on Ireland during the Second World War. Drawing on a wealth of archival material, this book provides a slice of real life during a pivotal episode in Irish and world history.